1997
DOI: 10.1017/s1355617797001690
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological function in patients with Gerstmann-Sträussler-Scheinker disease from the Indiana Kindred (F198S)

Abstract: Three patients with Gerstmann-Sträussler-Scheinker disease (GSS) caused by a serine-for-phenylalanine substitution at codon 198 of the prion protein gene (PRNP) were compared to 9 age- and education-matched non-mutation-carriers from the same large Indiana kindred (GSS–IK) on a comprehensive neuropsychological test battery. Clinically significant impairments in intelligence, secondary memory, attention and cognitive processing speed, executive ability, and manual motor skills were noted in 2 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The mutation reported herein is the first one to cause an amino acid substitution (G → V) in a short, antiparallel ␤-sheet domain comprising residues 128 to 131. 8 The impact of such mutation on PrP folding and processing remains undetermined. 14 In the proband, NFTs were observed in the hippocampus and entorhinal cortex.…”
Section: Commentmentioning
confidence: 99%
“…The mutation reported herein is the first one to cause an amino acid substitution (G → V) in a short, antiparallel ␤-sheet domain comprising residues 128 to 131. 8 The impact of such mutation on PrP folding and processing remains undetermined. 14 In the proband, NFTs were observed in the hippocampus and entorhinal cortex.…”
Section: Commentmentioning
confidence: 99%
“…More than 20 different mutations in the prion protein are known to be associated with inherited TSEs in humans (Collinge, 2001), i.e., the inherited form of CJD (Bell and Ironside, 1993;Spudich et al, 1995), the Gerstmann-Sträussler-Scheinker syndrome (GSS; Ghetti et al, 1995;Unverzagt et al, 1997), and fatal familial insomnia (FFI; Goldfarb et al, 1992;Gambetti et al, 1995). Interestingly, all disease-related point mutations in human PrP are located within segment 90-231, which forms the protease-resistant core of the PrP Sc oligomer (Safar et al, 1990, Weissmann et al, 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The PET tracer [ 18 F]flortaucipir was used to investigate the pattern of tau deposition in two GSS patients who carry the PRNP F198S mutation and are members of a pedigree that has been previously studied extensively from the clinical and neuropathological points of view [ 7 , 11 , 14 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gerstmann-Sträussler-Scheinker disease (GSS) [ 9 ] is a rare dominantly inherited prion protein (PrP) amyloidosis. GSS patients, from a large kindred, have been extensively studied in three generations [ 13 ]; they carry a TTC to TCC DNA change at codon 198 of the prion protein gene ( PRNP) resulting in a phenylalanine to serine substitution (F198S) in the prion protein [ 6 , 7 , 11 , 12 , 14 , 16 , 35 ]. Neuropathologic examinations in these patients have shown that the extracellular PrP amyloid coexists with a severe intraneuronal tau pathology, characterized by deposits of hyperphosphorylated tau and neurofibrillary tangles (NFT) in the cerebral gray matter, but not in the cerebellum [ 10 , 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation